Antimicrobial Susceptibility Pattern of Bacterial Isolates in Patients with Lower Respiratory Tract Infections: Life Sciences -Microbiology - Ravi, Monisha; Krishnasamy, Lakshmi; Krishnakumar, Sharanya (International Journal of Life Science and Pharma Research, 2023)
Lower respiratory tract infection (LRI) is one of the global public health problems accounting for millions of deathsannually. The present study aim is to determine bacterial pathogens’ bacteriological profile and antibiotic susceptibility patternaffecting the patients with LRI attending a tertiary care hospital. Two hundred and eight sputum samples were collected frompatients with signs and symptoms of LRI. The samples were processed in Microbiology laboratory for bacterial pathogens.Bacterial isolates were identified using standard microbiological techniques and antibiotic susceptibility testing was performedusing the Kirby-Bauer disc diffusion method. Klebsiella pneumoniae (39.6%), followed by Pseudomonas (32%), were the mostpredominant bacteria isolated in the present study. The other bacteria isolated were Escherichia coli (16.9%), Staphylococcusaureus (5.6%), Streptococcus species (1.8%), and Acinetobacter (3.7%). Gram-negative bacteria showed high drug resistance toampicillin and cephalosporins and maximum susceptibility to piperacillin-tazobactam, amikacin, and gentamicin. Most of theisolates showed resistance to the Beta-lactam group of antibiotics. The isolated bacterial pathogens’ resistance profile indicatesthe need for the appropriate diagnosis and antibiotic susceptibility testing before managing the cases.